ANALISIS KINERJA PROYEK BALAI SERBAGUNA BILA DITINJAU DARI BIAYA PROYEK (CPI) DENGAN METODE EARNED VALUE MANAGEMENT (EVM) - Yosef Afrianus Kelau; I Gede Ngurah Sunatha; I Gusti Agung Ayu Istri Lestari (Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
Time and cost are very influential on the success and failure of a project. Benchmark for project success is seen from the short completion with minimal costs without leaving the quality of the work. Systematic project management is needed to ensure that the project implementation time is in accordance with the contract or even faster so that the costs incurred can provide benefits. The purpose of this study was to determine the performance of the Balai Serbaguna project in terms of project costs and time. Performance analysis on the construction project of the Multipurpose Hall in Tabanan district using the Earned Value Management (EVM) Method. The Earned Value Management method uses three indicators in its calculation, namely: ACWP (Actual Cost Work Performance), BCWP (Budget Cost Work Performance), BCWS (Budget Cost Work Schedule). Project performance can be seen from the calculation of the CPI (Cost Performance Index). During the 8 weeks of the project implementation, it can be seen that the CPI performance in weeks 1, 2, 3, 7, and 8 of the CPI is <1, which means that the project implementation budget is greater than the planned budget, so the project is said to be not good in terms of costs. At week 4 and 5 the CPI is worth> 1, which means that the project implementation budget is smaller than the planned budget, which can be said to be good in terms of costs.